Risk Analysis of the Cooking Oil Industry in the Maloy Batuta Trans Kalimantan Special Economic Zone - Sampor Ali; Djoko Hananto; Daman Sudarman (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2024)
Management risk in cooking oil industry is important. This paper to analyze various risks faced by the palm oil-based cooking oil industry in the Maloy Batuta Trans Kalimantan Special Economic Zone (KEK MBTK), Kutai Timur, East Kalimantan, and to formulate mitigation strategies to support the sustainability of the area. The risks examined include fluctuations in Crude Palm Oil (CPO) prices, infrastructure limitations, environmental pressures, regulatory uncertainties, and social conflicts. The research employs a qualitative descriptive approach, collecting data through interviews, literature reviews, and document analysis. The findings indicate that infrastructure improvements, the adoption of environmentally friendly technologies, product diversification, and community involvement are key strategies for addressing these risks. The study concludes that an integrated risk management approach is crucial to enhancing the competitiveness of the cooking oil industry in KEK MBTK while fostering sustainable economic growth in Kutai Timur.